A circumscribed projection from the nucleus of the solitary tract to the nucleus ambiguus in the rat: anatomical evidence for somatostatin- 28-immunoreactive interneurons subserving reflex control of esophageal motility - Cunningham, ET (J Neurosci, 1989)
Axonal transport and immunohistochemical methods were used to investigate the anatomical and biochemical organization of projections from the nucleus of the solitary tract (NTS) to the rostral, esophageal, part of the nucleus ambiguus (NA) in the rat. Discrete iontophoretic deposits of a retrogradely transported tracer, fluorogold, placed in the rostral NA labeled a column of cells within the NTS, termed the central part of the NTS (after Ross et al., 1985), situated just medial to the solitary tract and extending from about 300 to 1000 microns rostral to the obex. Iontophoretic deposits of the anterogradely transported tracer, Phaseolus vulgaris-leucoagglutinin (PHA-L), placed in the central part of the NTS gave rise to dense and topographically restricted projections to the rostral NA. More caudal and ventral aspects of the NA did not receive prominent inputs from the central part of the NTS, and deposits that spared the central part of the NTS gave rise to only sparse projections to the rostral NA. Antisera against somatostatin-28 (SS-28) stained cell bodies within the central part of the NTS. In addition, a double-labeling procedure, capable of colocalizing anterogradely transported PHA-L and endogenous peptides to individual fibers and/or terminals, demonstrated an appreciable number of SS-28-immunoreactive terminals within the rostral NA that arose from the NTS. Correspondingly, unilateral lesions that involved the central part of the NTS resulted in a marked depletion of SS-28 immunoreactivity in the ipsilateral rostral NA. These data provide evidence for a discrete, partly somatostatinergic, projection from the central part of the NTS to the rostral NA. Anatomical and physiological studies implicating the central part of the NTS and the rostral NA in esophageal function suggest this pathway to be involved in the reflex control of esophageal motility.